ESG shareholder engagement and downside risk - Hoepner, AGF; Oikonomou, I; Sautner, Z; Starks, LT; Zhou, XY (Oxford University Press, 2023)
We show that engagement on environmental, social, and governance issues can benefit shareholders by reducing firms’ downside risks. We find that the risk reductions (measured using value at risk [VaR] and lower partial moments) vary across engagement types and success rates. Engagement is most effective in lowering downside risk when addressing environmental topics (primarily climate change). Further, targets with large downside risk reductions exhibit a decrease in environmental incidents after the engagement. We estimate that the VaR of engagement targets decreases by 9 percent of the standard deviation after successful engagements, relative to control firms.